Faktor-faktor Keberhasilan Implementasi Sedekah Sampah di RW 1 Kelurahan Peterongan, Kota Semarang - Dwi Endah; Heru Subaris Kasjono (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
The more intense of human’s activities, the higher of the waste will be yielded. Efforts are need-ed for waste management that is not giving pollution to environment, easy to be applied and ad-vantageous. Sedekah Sampah or Waste for Almsgiving is one alternative for that kind of waste management that has been implemented at RW 1 of Kelurahan Peterongan in Semarang City under the assistance of Cita Sehat Foundation (CSF) Semarang branch. The aims of this study that has been held in June 2014 at the implementation site of that waste program was to know the success factors and the knowledge, attitude and behavior about waste management that existing among the community. The study was a cross sectional designed quantitative one with sample size consisted of 70 householders who were obtained by simple random sample techni-que. The data were collected by using questionnaire and were analysed descriptively. The re-sults show that most of the respondents (60 %) manage their waste by following Sedekah Sam-pah system and the all remainder percentage (100 %) is also involved as participants of the system. The results also show that all of the respondents (100 %) have good level of knowledge and attitude, and factors affecting the implementation of sedekah Sampah program are: 96 % is because of its benefits, 20 % is in order to make the environment clean, and 17 % is because of its simplicity. The reason of the benefit is because they convince that Sedekah Sampah will give them a reward of goodness and also because the profit is used for mutual interest and success.